Reply to the letter: The evidence of Bayesian A/B testing in the contrast of clinical events by COVID-19 - Jeel Moya-Salazar (Asociación Colombiana de Infectología, 2021)
We reviewed the comments made by Cristian Ramos-Vera with great interest, and we thank him for his comments. His comments will allow us to lead the reading from the "stan-dard framework of frequentist statistics based on significan-ce assumptions" towards Bayesian models and thus avoid dichotomous biases for future interests in the manuscript.